GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Palm, mangrove and Podocarpaceae environments along the southwestern African coast during the Paleogene–Neogene transition - Moteng E. Moseri; Frank H. Neumann; Nikiwe Z. Ndlovu; Eugene W. Bergh; Louis Scott; Mabrouk Bachari; Marion K. Bamford; Tshiamo T. O. Mmatladi; Thokozani Mahlangu (Palynology, 2026)

Diabetic and overweight cats have altered gut microbial diversity and composition - Souvik Patra; Ursula H. Neumann; Chantal J. McMillan; Elisabeth R. Snead; Casey P. Shannon; Karen K. Lam; Prasanth K. Chelikani (The Veterinary Journal, 2026)

Non-decalcified human teeth sample preparation method for MALDI mass spectrometry imaging - Kayle J. Bender; Joanna E. Spurgeon; Chuo Ying Zhai; Manish Arora; Elizabeth K. Neumann (Analytica Chimica Acta, 2026)

Mycorrhizal identity and light shape tree seedling biomass responses in plant–soil feedbacks - Sarah McCarthy-Neumann; Katherine E. A. Wood; Richard K. Kobe (Plant and Soil, 2026)
Aims Plant–soil feedbacks (PSFs) are key drivers of forest composition and diversity, yet their direction and magnitude may depend on the mycorrhizal identity of interacting species, environmental conditions, and experimental context. Methods We conducted complementary greenhouse and field experiments using Acer rubrum L., Acer saccharum Marsh., Prunus serotina Ehrh. (all arbuscular mycorrhizal [AM] species), and Quercus alba L., and Quercus rubra L. (all ectomycorrhizal [EM] species) to test how biomass-based PSFs vary with mycorrhizal matching between seedlings and adult trees, light availability, and soil microbial communities. Seedlings were grown in soil conditioned by conspecifics, conmycorrhizal heterospecifics, or heteromycorrhizal heterospecifics under controlled and natural light regimes. Results Consistent with expectations, AM species consistently exhibited negative PSFs under low light, and EM species tended to show more positive PSFs, but this pattern was contingent on light and greenhouse versus field setting. For AM species, negative PSFs occurred primarily under low light and were neutralized or reversed under higher light. EM species showed generally more positive PSFs across light levels and settings, although species-specific differences emerged. PSFs were driven largely by conspecific soil conditioning, with limited influence from the mycorrhizal identity of heterospecific neighbors. Results from greenhouse versus field settings diverged, with field PSFs sometimes attenuated or reversed, particularly for Q. alba. Conclusions These findings highlight that biomass-based PSFs are not fixed species traits but context-dependent outcomes influenced by mycorrhizal type, light availability, and environmental setting. Incorporating these factors is essential for predicting how PSFs influence seedling recruitment, forest dynamics, and biodiversity.

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

TGFβ signalling pathway impacts brain metastases profiles in locally advanced colorectal cancer - Sven Jacob; Ilja Balonov; Vindi Jurinovic; Christian Heiliger; Tengis Tschaidse; Jörg Kumbrink; Thomas Kirchner; Jens Werner; Martin K. Angele; Marlies Michl; Jens Neumann (Clinical & Experimental Metastasis, 2024)
Rationale Colorectal Cancer (CRC) represents the third most common type of cancer in Germany and the second most common cancer-related cause of death worldwide. Distant metastases are still the main limit for patient survival. While liver metastases as well as peritoneal carcinomatosis can often either be resected or treated with systemic therapy, little options remain for brain metastases. Additionally, a number of studies has already investigated hepatic, peritoneal, pulmonary as well as continuing distant metastases in colorectal cancer. Yet, with respect to tumor biology and brain metastases, little is known so far. Material and methods Two cohorts, M0 without distant spread and BRA with brain metastases were build. RNA was isolated from paraffin embedded specimen. Gene expression was performed by an RNA NanoString-Analysis using the nCounter® PanCancer Progression Panel by NanoString-Technologies (Hamburg, Germany). Results were analysed by principal component analysis, gene expression and pathway analysis using commonly available databases such as KEGG as benchmark for comparison. Results We were able to determine a gene signature that provides a sophisticated group separation between M0 and BRA using principal component analysis. All genes with strong loading characteristics on principal component 1 were cross-referenced with the subsequently performed accurate gene set enrichment analysis (GSEA). The GSEA revealed a clear dysregulation of the TGFβ pathway in compared cohorts M0 and BRA. Interestingly, the targeted pathways analysis of the identified genes confirmed that in fact almost all strong loading genes of PC1 play a role in the TGFβ pathway. Conclusion Our results suggest the TGFβ pathway as a crucial player in the development of brain metastases in primary CRC. In some types of colorectal cancer, downregulation of the TGFβ pathway might hinder primary colorectal cancer to metastasize to the nervous system. While the paradoxical functioning of the TGFβ pathway is still not fully understood, these shed light on yet another clinical implication of this complex pathway.

Club cell protein (CC16) in serum as an effect marker for small airway epithelial damage caused by diesel exhaust and blasting fumes in potash mining - Savo Neumann; Swaantje Casjens; Frank Hoffmeyer; Katrin Rühle; Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Jörg Giesen; Volker Neumann; Dirk Taeger; Dirk Pallapies; Thomas Birk; et al. (International Archives of Occupational and Environmental Health, 2024)
Objective The effect marker club cell protein (CC16) is secreted by the epithelium of the small respiratory tract into its lumen and passes into the blood. Increased amounts of CC16 in serum are observed during acute epithelial lung injury due to air pollutants. CC16 in serum was determined as part of this cross-sectional study in underground potash miners on acute and chronic health effects from exposures to diesel exhaust and blasting fumes. Methods Nitrogen oxides, carbon monoxide, and diesel particulate matter were measured in 672 workers at a German potash mining site on a person-by-person basis over an early shift or midday shift, together with CC16 serum concentrations before and after the respective shift. CC16 concentrations and CC16 shift-differences were evaluated with respect to personal exposure measurements and other quantitative variables by Spearman rank correlation coefficients. CC16 shift-differences were modeled using multiple linear regression. Above-ground workers as reference group were compared to the exposed underground workers. Results Serum concentrations of CC16 were influenced by personal characteristics such as age, smoking status, and renal function. Moreover, they showed a circadian rhythm. While no statistically significant effects of work-related exposure on CC16 concentrations were seen in never smokers, such effects were evident in current smokers. Conclusion The small airways of current smokers appeared to be vulnerable to the combination of measured work-related exposures and individual exposure to smoking. Therefore, as health protection of smokers exposed to diesel exhaust and blasting fumes, smoking cessation is strongly recommended.

Assessment of climate extremes at the regional scale during the last millennium using an annually resolved stalagmite record - Tobias Kluge; Philipp Holz; Thomas Neumann; Elisabeth Eiche; Maximilian Schuh; Norbert Frank; Ronny Friedrich; Alexander Land; Mario Trieloff; Axel K. Schmitt (Earth and Planetary Science Letters, 2023)

Evaluating the addition of radar with optical data for vegetation mapping in a montane region in Sri Lanka - W. D. K. V. Nandasena; Lars Brabyn; Silvia Serrao-Neumann (Journal of Mountain Science, 2023)

Meteorological influences on airborne pollen and spores in Johannesburg (Gauteng), South Africa - Linus B. Ajikah; Sarah J. Roffe; Frank H. Neumann; Marion K. Bamford; Nanike Esterhuizen; Dilys Berman; Jonny Peter (Aerobiologia, 2023)
Airborne fungal spores and pollen (aerospora), synergistic with air pollution, are key triggers of allergic respiratory diseases. Effective diagnosis and treatment requires up-to-date location-specific knowledge on the temporal variability of aerospora types and levels. Johannesburg is the largest city in South Africa and has grown substantially in three decades, with changes in ground cover, population density and air pollution, yet until now, no continuous aerospora sampling has occurred. We present a daily two-year (August 2019–July 2021) aerospora assemblage for Johannesburg and explore temporal characteristics of 13 dominant aerospora in relation to daily meteorological variables (pressure, rainfall, relative humidity, temperature and wind characteristics). February–July, July–September and January-July represent high-risk periods for fungal spores [( Alternaria alternata (Fries. ex Keissler), Ascospores, Aspergillus niger (Van Tieghem) , Penicillium chrysogenum (Thom), Cladosporium graminum (Corda), Epicoccum nigrum (Link), Helminthosporium solani (Durieu and Montagne) Nigrospora sphaerica (Saccardo ex. Mason), Smuts Ustilago nuda ( Jensen ex. Rostrup) and Torula herbarum (Link)], trees ( Cupressus , Morus and Platanus ) and grass (Poaceae), respectively. Using a generalised additive model, results show that daily meteorological characteristics explained 7–32% of daily aerospora variability, with the largest effect on tree pollen. Rainfall, relative humidity and temperature influenced daily fungal spore and Poaceae counts, with moderate/low rainfall (

Impact of diesel exhaust exposure on urinary 1-hydroxypyrene in underground salt and potash workers - Swaantje Casjens; Savo Neumann; Katrin Rühle; Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Thomas Birk; Jörg Giesen; Volker Neumann; Dirk Pallapies; Jürgen Bünger; Heiko U. Käfferlein; et al. (International Journal of Hygiene and Environmental Health, 2023)

Optimized cleaning of conveyor belts using plasma-processed water assisted by optical detection of food residues - Julia Durek; Antje Fröhling; Frank Stüpmann; Sabine Neumann; Jörg Ehlbeck; Oliver K. Schlüter (Innovative Food Science & Emerging Technologies, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Underground salt and potash workers exposed to nitrogen oxides and diesel exhaust: assessment of specific effect biomarkers - Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Katrin Rühle; Annette M. Bachand; Lori Crawford; Kenneth A. Mundt; Jürgen Bünger; Dirk Pallapies; Dirk Taeger; Swaantje Casjens; Anja Molkenthin; et al. (International Archives of Occupational and Environmental Health, 2022)
Purpose Occupational exposure limits (OEL) for nitrogen oxides (NO, NO 2 ) and diesel exhaust (EC-DPM) were reassessed by the German authorities in 2016/2017. We performed a clinical cross-sectional study among salt and potash underground workers exposed to these substances at relatively high levels to examine possible indicators of acute effects on workers’ health. Methods We measured post- versus pre-shift differences in cardiovascular, inflammatory, immune, and respiratory effect biomarkers and assessed their associations with personal exposures measured during the same shift. We also compared post- versus pre-shift differences in biomarker levels between exposure groups defined based on work site and job type. Results None of the above-ground workers exceeded the OEL for NO 2 and only 5% exceeded the OEL for EC-DPM exposure. Among underground workers, 33% of miners and 7% underground maintenance workers exceeded the OEL for NO 2 ; the OEL for EC-DPM was exceeded by 56% of miners and 17% of maintenance workers. Some effect biomarkers (thrombocytes, neutrophils, MPO, TNF-α, IgE, FeNO) showed statistically significant differences between pre- versus post-shift measurements; however, there were no consistent associations between pre- and post-shift differences and exposure group or personal exposure measurements during the shift. Conclusions We did not find evidence of associations between workplace exposure to NO, NO 2 or EC-DPM and clinically relevant indicators of acute cardiovascular, inflammatory and immune, or respiratory effects among salt and potash underground workers in Germany.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

New phylogenetic insights into the African catfish families Mochokidae and Austroglanididae - Frederic D. B. Schedel; Albert Chakona; Brian L. Sidlauskas; Michael O. Popoola; Nadine Usimesa Wingi; Dirk Neumann; Emmanuel J. W. M. N. Vreven; Ulrich K. Schliewen (Journal of Fish Biology, 2022)
Several hundred catfish species (order: Siluriformes) belonging to 11 families inhabit Africa, of which at least six families are endemic to the continent. Although four of those families are well‐known to belong to the ‘Big‐Africa clade’, no previous study has addressed the phylogenetic placement of the endemic African catfish family Austroglanididae in a comprehensive framework with molecular data. Furthermore, interrelationships within the ‘Big‐Africa clade’, including the most diverse family Mochokidae, remain unclear. This study was therefore designed to help reconstruct inter‐ and intrarelationships of all currently valid mochokid genera, to infer their position within the ‘Big Africa clade’ and to establish a first molecular phylogenetic hypothesis of the relationships of the enigmatic Austroglanididae within the Siluriformes. We assembled a comprehensive mitogenomic dataset comprising all protein coding genes and representing almost all recognized catfish families ( N = 33 of 39) with carefully selected species ( N = 239). We recovered the monophyly of the previously identified multifamily clades ‘Big Asia’ and ‘Big Africa’ and determined Austroglanididae to be closely related to Pangasiidae, Ictaluroidea and Ariidae. Mochokidae was recovered as the sister group to a clade encompassing Auchenoglanididae, Claroteidae, Malapteruridae and the African Schilbeidae, albeit with low statistical support. The two mochokid subfamilies Mochokinae and Chiloglanidinae as well as the chiloglanid tribe Atopochilini were recovered as reciprocally monophyletic. The genus Acanthocleithron forms the sister group of all remaining Mochokinae, although with low support. The genus Atopodontus is the sister group of all remaining Atopochilini. In contrast to morphological reconstructions, the monophyly of the genus Chiloglanis was strongly supported in our analysis, with Chiloglanis macropterus nested within a Chiloglanis sublineage encompassing only other taxa from the Congo drainage. This is an important result because the phylogenetic relationships of C. macropterus have been controversial in the past, and because we and other researchers assumed that this species would be resolved as sister to most or all other members of Chiloglanis . The apparent paraphyly of Synodontis with respect to Microsynodontis provided an additional surprise, with Synodontis punu turning out to be the sister group of the latter genus.

Correction to: Coastal flood risk within a peri‑urban area: Sussex Inlet district, SE Australia - E. F. Asbridge; D. Low Choy; B. Mackey; S. Serrao-Neumann; P. Taygfeld; K. Rogers (Natural Hazards, 2022)

Cardiovascular risk prediction in healthy older people - Johannes T. Neumann; Le T. P. Thao; Emily Callander; Enayet Chowdhury; Jeff D. Williamson; Mark R. Nelson; Geoffrey Donnan; Robyn L. Woods; Christopher M. Reid; Katrina K. Poppe; Rod Jackson; Andrew M. Tonkin; et al. (GeroScience, 2022)
Identification of individuals with increased risk of major adverse cardiovascular events (MACE) is important. However, algorithms specific to the elderly are lacking. Data were analysed from a randomised trial involving 18,548 participants ≥ 70 years old (mean age 75.4 years), without prior cardiovascular disease events, dementia or physical disability. MACE included coronary heart disease death, fatal or nonfatal ischaemic stroke or myocardial infarction. Potential predictors tested were based on prior evidence and using a machine-learning approach. Cox regression analyses were used to calculate 5-year predicted risk, and discrimination evaluated from receiver operating characteristic curves. Calibration was also assessed, and the findings internally validated using bootstrapping. External validation was performed in 25,138 healthy, elderly individuals in the primary care environment. During median follow-up of 4.7 years, 594 MACE occurred. Predictors in the final model included age, sex, smoking, systolic blood pressure, high-density lipoprotein cholesterol (HDL-c), non-HDL-c, serum creatinine, diabetes and intake of antihypertensive agents. With variable selection based on machine-learning, age, sex and creatinine were the most important predictors. The final model resulted in an area under the curve (AUC) of 68.1 (95% confidence intervals 65.9; 70.4). The model had an AUC of 67.5 in internal and 64.2 in external validation. The model rank-ordered risk well but underestimated absolute risk in the external validation cohort. A model predicting incident MACE in healthy, elderly individuals includes well-recognised, potentially reversible risk factors and notably, renal function. Calibration would be necessary when used in other populations.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

100 Jahre Photogrammetrie-Innovation aus Heerbrugg - S. Heggli; K. Neumann; E. Voit (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2021)

Coastal flood risk within a peri-urban area: Sussex Inlet district, SE Australia - E. F. Asbridge; D. Low Choy; B. Mackey; S. Serrao-Neumann; P. Taygfeld; K. Rogers (Natural Hazards, 2021)

Human histamine H2 receptors can initiate cardiac arrhythmias in a transgenic mouse - U. Gergs; J. Weisgut; K. Griethe; N. Mißlinger; U. Kirchhefer; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Histamine is known to lead to arrhythmias in the human heart. A mouse model to mimic these effects has hitherto not been available but might be useful to study the mechanism(s) of H 2 -histamine receptor-induced arrhythmias and may support the search for new antiarrhythmic drugs. In order to establish such a model in mice, we studied here the incidence of cardiac arrhythmias under basal and under stimulated conditions in atrial and ventricular preparations from mice that overexpressed the human H 2 -histamine receptors in a cardiac-specific way (H 2 -TG) in comparison with their wild-type (WT) littermate controls. We had shown before that histamine exerted concentration and time-dependent positive inotropic and positive chronotropic effects only in cardiac preparations from H 2 -TG and not from WT. We noted under basal conditions (no drug addition) that right atrial preparations from H 2 -TG exhibited more spontaneous arrhythmias than right atrial preparations from WT. These arrhythmias in H 2 -TG could be blocked by the H 2 -histamine receptor antagonist cimetidine. In a similar fashion, histamine and dimaprit (an agonist at H 2 and not H 1 -histamine receptors) more often induced arrhythmias in right atrial preparations from H 2 -TG than from WT. To understand better the signal transduction mechanism(s) involved in these arrhythmias, we studied partially depolarized left atrial preparations. In these preparations, a positive inotropic effect of histamine was still present in the additional presence of 44 mM potassium ions (used to block sodium channels) in H 2 -TG but not WT and this positive inotropic effect could be blocked by cimetidine and this is consistent with the involvement of calcium ion channels in the contractile and thus might mediate also the arrhythmogenic effects of histamine in H 2 -TG. However, compounds reported to release histamine from cells and thereby leading to arrhythmias in humans, namely morphine, ketamine, and fentanyl, failed to induce a more pronounced positive inotropic effect in atrial preparations from H 2 -TG compared to WT, arguing against an involvement of histamine release in their proarrhythmic side effects in patients. Measuring left ventricular contractility in isolated retrogradely perfused hearts (Langendorff mode), we detected under basal conditions (no drug application) more spontaneous arrhythmias in hearts from H 2 -TG than from WT. In summary, we noted that overexpression of human H 2 -histamine receptors in a novel transgenic animal model can lead to arrhythmias. We suggest that this model might be useful to understand the mechanism(s) of histamine-induced cardiac arrhythmias in humans better in a molecular way and may be of value to screen novel antiarrhythmic drugs.

The place beyond the trees: renewed excavations of the Middle Stone Age deposits at Olieboomspoort in the Waterberg Mountains of the South African Savanna Biome - A. Val; P. de la Peña; M. Duval; S. Bansal; F. Colino; J. Culey; T. Hodgskiss; P. Morrissey; A. Murray; M. Murungi; F.H. Neumann; K. Shadrach; et al. (Archaeological and Anthropological Sciences, 2021)
Olieboomspoort is one of the few rock shelters in the vast interior of southern Africa documenting pulses of occupation from the Acheulean until the end of the Later Stone Age. Revil Mason excavated the site in 1954 and attributed the large Middle Stone Age (MSA) lithic assemblage to his middle phase of the so-called Pietersburg Industry. Recent work at the site has focused on the Holocene layers, but little is known about the earlier phases of shelter use. Here, we provide some background to the shelter, give a history of past research and present initial results following renewed fieldwork at the site. The MSA deposits contain abundant lithic artefacts and ochre, and we present an initial description of these cultural remains. Palynological analysis reveals limited potential for palaeoenvironmental reconstructions, but some faunal remains indicate open grasslands. We dated two equid teeth that provided highly consistent combined U-series-ESR estimates, resulting in a mean age of 150 ± 14 ka (1σ). Even when considering potential sources of uncertainty such as variations in water-intake, these fossils can securely be dated to Marine Isotopic Stage 6. Our reappraisal of site formation processes highlights the fact that the archaeological assemblage is strongly time-averaged. We discuss these different results in the context of a recently rekindled interest in the so-called Pietersburg Industry.

Cost‐effectiveness of longitudinal surveillance for Piscirickettsia salmonis using qPCR in Atlantic salmon farms ( Salmo salar ) in Chile - Marina K. V. C. Delphino; Fernando O. Mardones; Joaquin Neumann Heise; Alicia Gallardo; Daniel Jimenez; Andrea Peña; Marco Rozas‐Serri; Ian A. Gardner (Journal of Fish Diseases, 2021)
Costs of diagnostic testing including sample collection, sampling frequency and sample size are an important consideration in the evaluation of the economic feasibility of alternative surveillance strategies for detection of infectious diseases in aquatic animals. In Chile, Piscirickettsia salmonis is the primary reason for antibiotic treatments in farmed Atlantic salmon. In 2012, a surveillance and control programme for piscirickettsiosis was established with an overall goal of reducing antibiotic use. The present study estimated the cost‐effectiveness of different sampling frequencies and sample sizes to achieve at least 95% confidence of early detection of P. salmonis at the netpen and farm levels using a validated qPCR test. We developed a stochastic model that incorporated variability in test accuracy, within‐pen prevalence and sampling costs. Our findings indicated that the current piscirickettsiosis surveillance programme based on risk‐based sampling of five moribund or dead fish from 2 to 3 netpens is cost‐effective and gives a high probability of detection of P. salmonis in Atlantic salmon farms in Chile at both the netpen and farm levels. Results from this study should incentivize salmon farmers to establish cost‐effective strategies for early detection of P. salmonis infection and the application of this approach to other highly infectious diseases.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Nitrogen isotope values of Pennisetum glaucum (pearl millet) grains: towards a reconstruction of past cultivation conditions in the Sahel, West Africa - Amy K. Styring; Amadou M. Diop; Amy Bogaard; Louis Champion; Dorian Q. Fuller; Nikolas Gestrich; Kevin C. Macdonald; Katharina Neumann (Vegetation History and Archaeobotany, 2019)

Time and laser ranging: a window of opportunity for geodesy, navigation, and metrology - P. Exertier; A. Belli; E. Samain; W. Meng; H. Zhang; K. Tang; A. Schlicht; U. Schreiber; U. Hugentobler; I. Prochàzka; X. Sun; J. F. McGarry; et al. (Journal of Geodesy, 2019)

Contrasting arsenic cycling in strongly and weakly stratified contaminated lakes: Evidence for temperature control on sediment–water arsenic fluxes - P. M. Barrett; E. A. Hull; K. Burkart; O. Hargrave; J. McLean; V. F. Taylor; B. P. Jackson; J. E. Gawel; R. B. Neumann (Limnology and Oceanography, 2019)
Arsenic contamination of lakebed sediments is widespread due to a range of human activities, including herbicide application, waste disposal, mining, and smelter operations. The threat to aquatic ecosystems and human health is dependent on the degree of mobilization from sediments into overlying water columns and exposure of aquatic organisms. We undertook a mechanistic investigation of arsenic cycling in two impacted lakes within the Puget Sound region, a shallow weakly stratified lake and a deep seasonally stratified lake, with similar levels of lakebed arsenic contamination. We found that the processes that cycle arsenic between sediments and the water column differed greatly in shallow and deep lakes. In the shallow lake, seasonal temperature increases at the lakebed surface resulted in high porewater arsenic concentrations that drove larger diffusive fluxes of arsenic across the sediment–water interface compared to the deep, stratified lake where the lakebed remained ~10°C cooler. Plankton in the shallow lake accumulated up to an order of magnitude more arsenic than plankton in the deep lake due to elevated aqueous arsenic concentrations in oxygenated waters and low phosphate : arsenate ratios in the shallow lake. As a result, strong arsenic mobilization from sediments in the shallow lake was countered by large arsenic sedimentation rates out of the water column driven by plankton settling.

Correction to: Diel plant water use and competitive soil cation exchange interact to enhance NH4+ and K+ availability in the rhizosphere - Javier F. Espeleta; Zoe G. Cardon; K. Ulrich Mayer; Rebecca B. Neumann (Plant and Soil, 2018)

Assessment of Eutrophication Abatement Scenarios for the Baltic Sea by Multi-Model Ensemble Simulations - H. E. Markus Meier; Moa K. Edman; Kari J. Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2018)

Diel plant water use and competitive soil cation exchange interact to enhance NH4 + and K+ availability in the rhizosphere - Javier F. Espeleta; Zoe G. Cardon; K. Ulrich Mayer; Rebecca B. Neumann (Plant and Soil, 2017)

No spatial patterns for early nectar storage in honey bee colonies - M. Eyer; M. K. Greco; J. Lang; P. Neumann; V. Dietemann (Insectes Sociaux, 2016)

Benefits of greenhouse gas mitigation on the supply, management, and use of water resources in the United States - K. Strzepek; J. Neumann; J. Smith; J. Martinich; B. Boehlert; M. Hejazi; J. Henderson; C. Wobus; R. Jones; K. Calvin; D. Johnson; E. Monier; et al. (Climatic Change, 2015)

Y-P30 promotes axonal growth by stabilizing growth cones - Janine R. Neumann; Suvarna Dash-Wagh; Kay Jüngling; Teresa Tsai; Martin Meschkat; Andrea Räk; Sabine Schönfelder; Christian Riedel; Mohammad I. K. Hamad; Stefan Wiese; Hans-Christian Pape; Kurt Gottmann; et al. (Brain Structure and Function, 2015)

Genome wide association mapping to identify aluminium tolerance loci in bread wheat - S. Navakode; K. Neumann; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2014)

Darbepoetin inhibits proliferation of hepatic cancer cells in the presence of TGF-β - Sabrina Ehnert; Thomas Freude; Carmen Eicher; Britta Burkhardt; Juan J. Martínez Sánchez; Jan Neumann; Ruben Mühl-Benninghaus; Steven Dooley; Stefan Pscherer; Andreas K. Nussler (Archives of Toxicology, 2014)

An association mapping analysis of dormancy and pre-harvest sprouting in wheat - M. A. Rehman Arif; K. Neumann; M. Nagel; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2012)

Molecular markers in management of ex situ PGR – A case study - Andreas Börner; Elena K Khlestkina; Sabina Chebotar; Manuela Nagel; Mian Abdur Rehman Arif; Kerstin Neumann; Borislav Kobiljski; Ulrike Lohwasser; Marion S Röder (Journal of Biosciences, 2012)

Performance of a novel microarray multiplex PCR for the detection of 23 respiratory pathogens (SYMP-ARI study) - S. Bierbaum; N. Königsfeld; N. Besazza; K. Blessing; G. Rücker; U. Kontny; R. Berner; M. Schumacher; J. Forster; V. Falcone; C. Sand; A. Essig; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Genetic studies of seed longevity in hexaploid wheat using segregation and association mapping approaches - M. A. Rehman Arif; M. Nagel; K. Neumann; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2012)

Strong decline of gene diversity in local populations of the highly endangered Common hamster (Cricetus cricetus) in the western part of its European range - M. J. J. La Haye; K. Neumann; H. P. Koelewijn (Conservation Genetics, 2012)

Comparative analysis of phase I and II enzyme activities in 5 hepatic cell lines identifies Huh-7 and HCC-T cells with the highest potential to study drug metabolism - Jie Lin; Lilianna Schyschka; Ruben Mühl-Benninghaus; Jan Neumann; Liping Hao; Natascha Nussler; Steven Dooley; Liegang Liu; Ulrich Stöckle; Andreas K. Nussler; Sabrina Ehnert (Archives of Toxicology, 2012)

Foraging behavior of golden hamsters (Mesocricetus auratus) in the wild - S. C. Larimer; P. Fritzsche; Z. Song; J. Johnston; K. Neumann; R. Gattermann; M. E. McPhee; R. E. Johnston (Journal of Ethology, 2011)

The alternative Pharaoh approach: stingless bees mummify beetle parasites alive - Mark K. Greco; Dorothee Hoffmann; Anne Dollin; Michael Duncan; Robert Spooner-Hart; Peter Neumann (The Science of Nature, 2010)

Methods from the Theory of Random Heterogeneous Media for Quantifying Myocardial Morphology in Normal and Dilated Hearts - Rudolf Karch; Friederike Neumann; Robert Ullrich; Georg Heinze; Josef Neumüller; Bruno K. Podesser; Martin Neumann (Annals of Biomedical Engineering, 2010)

Hitze induzierte Transgeninaktivierung in Solanaceen - J. Huckauf; N. Knöchel; T. Latzkow; S. Walter; S. Kerbach; S. Köhne; K. Neumann; I. Broer (Journal of Consumer Protection and Food Safety, 2007)

Bee-hawking by the wasp, Vespa velutina, on the honeybees Apis cerana and A. mellifera - K. Tan; S. E. Radloff; J. J. Li; H. R. Hepburn; M. X. Yang; L. J. Zhang; P. Neumann (The Science of Nature, 2007)

Individual versus social pathway to honeybee worker reproduction (Apis mellifera): pollen or jelly as protein source for oogenesis? - M. O. Schäfer; V. Dietemann; C. W. W. Pirk; P. Neumann; R. M. Crewe; H. R. Hepburn; J. Tautz; K. Crailsheim (Journal of Comparative Physiology A, 2006)

Effects of boron on somatic embryogenesis of Daucus carota - K. Mashayekhi; K.H. Neumann (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Osteoprotegerin reduces the loss of periarticular bone mass in primary and secondary spongiosa but does not influence inflammation in rat antigen-induced arthritis - T. Neumann; P. Oelzner; P. K. Petrow; K. Thoss; G. Hein; G. Stein; R. Bräuer (Inflammation Research, 2006)

Genetic spatial structure of European common hamsters ( Cricetus cricetus ) — a result of repeated range expansion and demographic bottlenecks - K. NEUMANN; J. R. MICHAUX; S. MAAK; H. A. H. JANSMAN; A. KAYSER; G. MUNDT; R. GATTERMANN (Molecular Ecology, 2005)
The spatial genetic structure of common hamsters ( Cricetus cricetus ) was investigated using three partial mitochondrial (mt) genes and 11 nuclear microsatellite loci. All marker systems revealed significant population differentiation across Europe. Hamsters in central and western Europe belong largely to two allopatric mitochondrial lineages south and northwest of the Carpathian and Sudetes. The southern group, ‘Pannonia’, comprises populations inside the Carpathian basin (Czech Republic, Hungary) while the second group, ‘North’, includes hamsters from Belgium, the Netherlands, France, and Germany. Isolation of the lineages is maintained by a combination of geographical and ecological barriers. Both main phylogeographical groups show signs of further subdivision. North is separated into highly polymorphic central German and less polymorphic western populations, which most likely split during late glacial expansion (15 000–10 000 bp ). Clock estimates based on haplotype distributions predict a divergence of the two major lineages 85 000–147 000 bp . Expansion times fall during the last glaciation (115 000–10 000 bp ) corroborating fossil data, which identify Cricetus cricetus as characteristic of colder climatic phases. Despite the allopatry of mt haplotypes, there is an overlap of nuclear microsatellite alleles between phylogeographical units. Although there are strong evidence that Pannonian hamsters have persisted inside the Carpathian basin over the last 50 000 years, genetic differentiation among European hamsters has mainly been caused by immigration from different eastern refugia. Possible source populations are likely to be found in the Ukrainian and the southern Russian plains — core areas of hamster distribution. From there, hamsters have repeatedly expanded during the Quaternary.

Factors influencing long-term survival in mesothelioma patients?results of the German mesothelioma register - V. Neumann; A. Rtten; M. Scharmach; K.-M. Mller; M. Fischer (International Archives of Occupational and Environmental Health, 2004)

Multiple bottlenecks in threatened western European populations of the common hamster Cricetus cricetus (L.) - K. Neumann; H. Jansman; A. Kayser; S. Maak; R. Gattermann (Conservation Genetics, 2004)

A multimodal brain-based feedback and communication system - Thilo Hinterberger; Nicola Neumann; Mirko Pham; Andrea Kbler; Anke Grether; Nadine Hofmayer; Barbara Wilhelm; Herta Flor; Niels Birbaumer (Experimental Brain Research, 2004)

Biomonitoring of aromatic amines VI: determination of hemoglobin adducts after feeding aniline hydrochloride in the diet of rats for 4 weeks - I. Zwirner-Baier; K. Deckart; R. Jckh; H.-G. Neumann (Archives of Toxicology, 2003)

The integration of a major hepatitis B virus gene into cell-cycle synchronized carrot cell suspension cultures and its expression in regenerated carrot plants - J. Imani; A. Berting; S. Nitsche; S. Schaefer; W. H. Gerlich; K.-H. Neumann (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Somatic embryogenesis and DNA organization of genomes from selected Daucus species - J. Imani; L. Tran Thi; G. Langen; B. Arnholdt-Schmitt; S. Roy; C. Lein; A. Kumar; K.-H. Neumann (Plant Cell Reports, 2001)

Malignant mesothelioma - German mesothelioma register 1987-1999 - V. Neumann; S. Günther; K.-M. Müller; M. Fischer (International Archives of Occupational and Environmental Health, 2001)

Characterization of a novel 21-kb deletion, CFTRdele2,3(21 kb), in the CFTR gene: a cystic fibrosis mutation of Slavic origin common in Central and East Europe - T. Dörk; M. Macek Jr; F. Mekus; B. Tümmler; J. Tzountzouris; T. Casals; A. Krebsová; M. Koudová; I. Sakmaryová; M. Macek Sr; V. Vávrová; D. Zemková; et al. (Human Genetics, 2000)

Niederländisch-Deutscher Kartographiekongress/48. Deutscher Kartographentag in Maastricht, 17.–20. Mai 1999 - Joachim Neumann; Gudrun K. Zögner; Miroslav Mikšovský; Christian Häberling (KN - Journal of Cartography and Geographic Information, 1999)

Chlororganic Pesticides and Polychlorinated Biphenyls in Breast Tissue of Women with Benign and Malignant Breast Disease - S. Güttes; K. Failing; K. Neumann; J. Kleinstein; S. Georgii; H. Brunn (Archives of Environmental Contamination and Toxicology, 1998)

Annexin V and vesicle membrane electroporation - K. Tönsing; S. Kakorin; E. Neumann; S. Liemann; R. Huber (European Biophysics Journal, 1997)

Productive expression state confers resistance of human immunodeficiency virus (HIV)-2-infected lymphoma cells against superinfection by HIV-1 - G. K. von Dalnok; Andrea Kleinschmidt; M. Neumann; Christine Leib-Moesch; V. Erfle; Ruth Brack-Werner (Archives of Virology, 1993)

Artificial neural network classification of Drosophila courtship song mutants - Eric K. Neumann; David A. Wheeler; Adam S. Bernstein; Jamie W. Burnside; Jeffrey C. Hall (Biological Cybernetics, 1992)

Colonization of adrenal glands and ovaries of mice by variants of HSV 1 and 2 - H. Wiegand; H. P. Dienes; P. Schirmacher; J. Podlech; K. Bohl; M. Bohle; D. Neumann-Haefelin; D. Falke (Archives of Virology, 1991)

Tödliches Lungenödem, angeblich infolge Lösungsmittelvergiftung - W. Neumann; K. Beyer (Archives of Toxicology, 1944)